Exogenously Applied Plant Growth Regulators Enhance the Morpho-Physiological Growth and Yield of Rice under High Temperature - Fahad, Shah; Hussain, Saddam; Saud, Shah; Hassan, Shah; Ihsan, Zahid; Shah, Adnan N.; Wu, Chao; Yousaf, Muhammad; Nasim, Wajid; Alharby, Hesham; Alghabari, Fahad; Huang, Jianliang (Frontiers in Plant Science, 2016)
A 2-year experiment was conducted to ascertain the effects of exogenously applied plant growth regulators (PGR) on rice growth and yield attributes under high day (HDT) and high night temperature (HNT). Two rice cultivars (IR-64 and Huanghuazhan) were subjected to temperature treatments in controlled growth chambers and four different combinations of ascorbic acid (Vc), alpha-tocopherol (Ve), brassinosteroids (Br), methyl jasmonates (MeJA), and triazoles (Tr) were applied. High temperature severely affected rice morphology, and also reduced leaf area, above-, and below-ground biomass, photosynthesis, and water use efficiency, while increased the leaf water potential of both rice cultivars. Grain yield and its related attributes except number of panicles, were reduced under high temperature. The HDT posed more negative effects on rice physiological attributes, while HNT was more detrimental for grain formation and yield. The Huanghuazhan performed better than IR-64 under high temperature stress with better growth and higher grain yield. Exogenous application of PGRs was helpful in alleviating the adverse effects of high temperature. Among PGR combinations, the Vc+Ve+MejA+Br was the most effective treatment for both cultivars under high temperature stress. The highest grain production by Vc+Ve+MejA+Br treated plants was due to enhanced photosynthesis, spikelet fertility and grain filling, which compensated the adversities of high temperature stress. Taken together, these results will be of worth for further understanding the adaptation and survival mechanisms of rice to high temperature and will assist in developing heat-resistant rice germplasm in future.